Interface Engineering of Hierarchical Branched Mo‐Doped Ni3S2/NixPy Hollow Heterostructure Nanorods for Efficient Overall Water Splitting. Issue 17 (16th March 2020) - Luo, Xu; Ji, Pengxia; Wang, Pengyan; Cheng, Ruilin; Chen, Ding; Lin, Can; Zhang, Jianan; He, Jianwei; Shi, Zuhao; Li, Neng; Xiao, Shengqiang; Mu, Shichun
Abstract: Rational design and construction of bifunctional electrocatalysts with excellent activity and durability is imperative for water splitting. Herein, a novel top‐down strategy to realize a hierarchical branched Mo‐doped sulfide/phosphide heterostructure (Mo‐Ni3 S2 /Ni x P y hollow nanorods), by partially phosphating Mo‐Ni3 S2 /NF flower clusters, is proposed. Benefitting from the optimized electronic structure configuration, hierarchical branched hollow nanorod structure, and abundant heterogeneous interfaces, the as‐obtained multisite Mo‐Ni3 S2 /Ni x P y /NF electrode has remarkable stability and bifunctional electrocatalytic activity in the hydrogen evolution reaction (HER)/oxygen evolution reaction (OER) in 1 m KOH solutions. It possesses an extremely low overpotential of 238 mV at the current density of 50 mA cm −2 for OER. Importantly, when assembled as anode and cathode simultaneously, it merely requires an ultralow cell voltage of 1.46 V to achieve the current density of 10 mA cm −2, with excellent durability for over 72 h, outperforming most of the reported Ni‐based bifunctional materials. Density functional theory results further confirm that the doped heterostructure can synergistically optimize Gibbs free energies of H and O‐containing intermediates (OH*, O*, and OOH*) during HER and OER processes, thus accelerating the catalytic kinetics of electrochemical water splitting. This work demonstrates the importance of the rational combination of metal doping and interface engineering for advanced catalytic materials. Abstract : Well‐designed hierarchical branched Mo‐Ni3 S2 /Ni x P y /NF hollow heterostructure nanorods, derived from an Ni3 S2 nanosheet network modulated by Mo and P elements, effectively boost the hydrogen evolution reaction/oxygen evolution reaction activity and stability under alkaline conditions.